Analisis Kepuasan Mahasiswa terhadap Service Quality Fakultas Tarbiyah IAIN Sorong - Hikmah, Afroh Nailil; Azis, Suci Indah Permata Hati (MISOOL: Jurnal Pendidikan Dasar, 2023)
The purpose of this study was to find out how the level of satisfaction of PGMI students with Tarbiyah faculty services was in accordance with student experiences related to Tarbiyah faculty services at IAIN Sorong. The results of this study indicate that the services provided by the Tarbiyah faculty to PGMI students which consist of five aspects indicate that the reliability aspect of the lecturers is 49.5%, the staff/educational personnel is 40.9% and the Tarbiyah Faculty 46.2% say good. of services received by students. Aspects of responsiveness from lecturers as much as 49.3%, staff/education personnel as much as 45.9%, and faculty of tarbiyah as much as 35.8% said they were good at the services received by students. Aspects of certainty from lecturers as much as 41.2% said it was very good for the services received by students while 45.2% of staff/educational staff said, and Tarbiyah faculty 42.9% said they were good for the services received by students. Aspects of empathy from lecturers as much as 47.0%, staff/education personnel as much as 45.8%, and Tarbiyah faculty as much as 41.6% both towards the services received by students. And aspects of physical evidence from lecturers as much as 43.7%, and Tarbiyah faculties as much as 40% said it was very good for the services received by students while 49.3% of staff/educational staff said they were good for the services received by students. When viewed from the results of the study as a whole, shows that student satisfaction includes the achievement of being satisfied to very satisfied with the services received by students